Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Bank Riau Kepri Cabang Bagan Siapi Api - Hendrayani, Hendrayani (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
This research was conducted on At PT. Bank Riau Kepri Branch Sian Api. The purpose of this study was to determine the effect of work motivation on employee performance at PT. Bank Riau Kepri Branch Sian Api. The population in this study amounted to 33 people. In this study, sampling using samples saturated or census, which is as many as 33 people. The data used are primary and secondary data with analysis using simple linear regression. The results showed that the motivation of work affect the performance of employees. The amount of influence of organizational culture on employee performance is 60.1% while the rest of 39.1% describe other independent variables that are not observed in this study.